Assessment and development of physical education teachers’ physical literacy: a systematic review - Yin, Hang; Omar Dev, Roxana Dev; Soh, Kim Geok; Li, Fangyi; Lian, Menglong; Lian, Menglong (Public Library of Science, 2024)
In recent years, physical literacy (PL) has gained a great deal of attention in global academia. Children’s physical activity (PA) participation is severely underrepresented today, and students’ participation in PA and PL level development is strongly dependent on the PL levels of PE teachers. This study aims to offer information for PE teachers to improve their PL levels and for the future development of tools to assess the PL of PE teachers through a systematic review of studies assessing PL of PE teachers. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) was used to conduct a comprehensive and systematic search in six databases—Web of Science, Scopus, ScienceDirect, PubMed, ProQuest; and SportDiscus, and a total of 671 papers were retrieved, but after removing duplicates, article identification, and screening only eight papers met the inclusion criteria. This study’s results indicate a paucity of research related to PL among PE teachers, focusing on children, students, older adults, and children with disabilities. PE teachers performed poorly in the physical competence domain and better in the cognitive and affective domains, with a moderate level of overall PL. Only one instrument is currently available to assess PE teachers’ (perceived) PL, and other studies have used instrument components. Therefore, it was concluded that the current PE teachers’ PL level is not high. Also, because the concept of PL among PE teachers has not been standardized, no tool has been developed to evaluate the PL of PE teachers comprehensively and systematically. The CPD (continuing professional development) is considered an effective means of enhancing PL among PE teachers, and research should prioritize the development of CPD programs and tools that are specifically tailored to assess PL among PE teachers in the future.